Innovative Techniques Associated with Traditional Abdominal Surgery in Complex Pediatric Cases: A Tertiary Center Experience - Rebecca Pulvirenti; Costanza Tognon; Silvia Bisoffi; Filippo Ghidini; Federica De Corti; Francesco Fascetti Leon; Luca Maria Antoniello; Piergiorgio Gamba (MDPI AG, 2021)
Pediatric abdominal surgery is constantly evolving, alongside the advent of new surgical technologies. A combined use of new tools and traditional surgical approaches can be useful in the management of complex cases, allowing less invasive procedures and sometimes even avoiding multiple interventions. This combination of techniques has implications even from the anesthetic point of view, especially in post-operative pain control. Thereby, tertiary level centres, including highly-specialized professionals and advanced equipment, can maximize the effectiveness of treatments to improve the final outcomes. Our paper aims to present some possible combinations of techniques recently used at our institution to provide a one-session, minimally invasive treatment within different areas of abdominal surgery.